Réponses

2013-08-02T21:55:07+02:00

2)  a.  Pour   x  →  3x + 5,       on a    a  =  3   et   b  =  5

 

    b.  Pour   x  →  x − 7,          on a    a  =  1   et   b  = −7

 

    c.  Pour   x  →  3 − 2x,        on a    a  = −2  et   b  =  3

 

    d.  Pour   x  → −4 + 2x/3,    on a    a  = 2/3  et   b  = −4

 

 

 

3)  a.  f(x)  =  3/2 (2x − 6)

                =  3x − 9

 

         qui est une fonction affine car de la forme   f(x)  =  ax + b

         avec   a  =  3      et      b  = −9

 

 

    b.  g(x)  =  5(x − 1) − 3(2x − 5)

                =  5x − 5 − 6x + 15

                =  −x + 10

 

         qui est une fonction affine car de la forme   g(x)  =  ax + b

         avec    a  = −1    et     b  =  10